DYNAMIC APPROACH AND COST ANALYSIS FOR OPTIMUM INSULATION THICKNESSES OF THE BUILDING EXTERNAL WALLS - Ozel, Meral (Gazi Univ, Fac Engineering Architecture, 2008)
The optimum thickness of insulation applying on external walls of building was investigated under dynamic thermal conditions. Therefore, the yearly heating transmission load was calculated by using an implicit finite differences method under steady periodic conditions. Calculations were done by considering external environment conditions of Elazig city. Extruded polystyrene was used as the insulation material, and coal, fuel-oil and natural gas were used as fuel. Then, cost analysis was done for a south facing wall insulated on outside. The optimum insulation thicknesses, the energy savings and payback periods were calculated for every fuel type. As result, optimum insulation thickness for Elazig was obtained to be 0.040 m when natural gas was used.
Keywords: Insulation thickness; building wall; yearly heating load; cost analysis